Optimizing the Clinical Impact of CAR-T Cell Therapy in B-Cell Acute Lymphoblastic Leukemia: Looking Back While Moving Forward - Safarzadeh Kozani, Pouya; Safarzadeh Kozani, Pooria; Rahbarizadeh, Fatemeh (Frontiers in Immunology, 2021)
Chimeric antigen receptor T-cell (CAR-T) therapy has been successful in creating extraordinary clinical outcomes in the treatment of hematologic malignancies including relapsed or refractory (R/R) B-cell acute lymphoblastic leukemia (B-ALL). With five FDA approvals so far, CAR-T therapy is recognized as an alternative treatment option for particular patients with certain conditions of B-ALL, diffuse large B-cell lymphoma, mantle cell lymphoma, follicular lymphoma, or multiple myeloma. However, CAR-T therapy for B-ALL can be surrounded by challenges such as various adverse events including the life-threatening cytokine release syndrome (CRS) and neurotoxicity, B-cell aplasia-associated hypogammaglobulinemia and agammaglobulinemia, and the alloreactivity of allogeneic CAR-Ts. Furthermore, recent advances such as improvements in media design, the reduction of ex vivo culturing duration, and other phenotype-determining factors can still create room for a more effective CAR-T therapy in R/R B-ALL. Herein, we review preclinical and clinical strategies with a focus on novel studies aiming to address the mentioned hurdles and stepping further towards a milestone in CAR-T therapy of B-ALL.